Double-negative T cells in pediatric rheumatic diseases - Dimitri Poddighe; Tilektes Maulenkul; Kuanysh Dossybayeva; Gulsamal Zhubanova; Zaure Mukusheva; Lyudmila Akhmaltdinova (Clinical and Experimental Pediatrics)
Double-negative (CD4-CD8-) T (DNT) cells have been implicated in autoimmune lymphoproliferative syndrome (ALPS), where their expansion inside the circulating pool of T cells represents a diagnostic criterion. Recent experimental evidence has supported the immunomodulatory roles of DNT cells, and studies in adult patients have suggested that they may be altered in some immune-mediated conditions. This study aimed to retrieve available data on circulating DNT cells in pediatric rheumatic disorders that do not arise in the context of ALPS through a systematic literature review of 3 scientific databases (PubMed, Scopus, and Web of Science). The final output of the systematic literature search consisted of 8 manuscripts, including cross-sectional (n=6) and longitudinal (n=2) studies. Overall, the pooled population of patients includes children affected with pediatric systemic lupus erythematosus (n= 104), juvenile idiopathic arthritis (n=92), Behçet's disease (n=15), mixed connective tissue disease (n=8), juvenile dermatomyositis (n=6), and Kawasaki disease/multisystem inflammatory disease in children (n=1 and n=14, respectively); moreover, one study also included 11 children with a high titer of antinuclear antibody but no diagnosis of rheumatic disease. All studies except one included a control group. The number of DNT cells were increased in most studies of children with rheumatic diseases. Even if such a limited number of studies and their great heterogeneity in several methodological aspects do not allow for reliable conclusions about the relevance of DNT cells in specific rheumatic conditions in children, this cell population deserves further investigation in this pathological setting through well-designed clinical studies.